STRUCTURAL RELIABILITY OPTIMIZATION DESIGN OF REINFORCED SHELL MODEL BASED ON ADAPTIVE SURROGATE MODEL - LIU YuZhuo; CAO LiXiong; WU JianGuo; LI HaiBo (Jixie qiangdu)
Reinforced shell structure is widely used in aerospace load-bearing structures because its high specific stiffness and specific strength.By considering the uncertainty and risk factors in the structural parameters，the Reliability-Based Design Optimization （RBDO） can avoid the overly conservative design of the structure and ensure its reliability and safety.An efficient RBDO method based on adaptive agent model was proposed.This method solves the problem of lightweight design of reinforced shell structure under buckling reliability constraints.The adaptive addition of sample points was implemented through the expected feasibility function criterion，and the discrete variables was continued by constructing piecewise functions.This increases optimization efficiency while ensuring the reliability of design results.Finally，the effectiveness of the proposed method is verified by comparing the RBDO results with the deterministic optimization results.